STRATEGI KOMUNIKASI PEMASARAN DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN ROKAN HULU DALAM MENINGKATKAN KUNJUNGAN WISATA PADA OBJEK WISATA AIRPANAS HAPANASAN - Muhammad Hanafi; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Tourism is one of the new industries which are able to accelerate economic growth and employment, boosting incomes, living standards and to stimulate other productive sectors. This prompted the Department of Culture and Tourism Rokan Hulu to create the attraction Airpanas Hapanasan with the aim to increase the budget and make the area one of the leading tourist attraction in the province of Riau. In increasing the number of visitors needed an effective marketing strategy to create attraction. The aim of this study was to determine how the marketing strategy undertaken by the Department of Culture and Tourism Rokan Hulu in increasing tourist arrivals area and outside the region. In addition, this study also aims to mengetehaui factors supporting and inhibiting factors in the implementation of marketing strategies.This study used qualitative research methods. Subjects in this study consisted of seven people and data collection techniques are grouped into three sections, namely; in-depth interviews, observation, and documentation. This study uses data analysis interactive model of Miles and Hubermen, using a technique that checks the validity of the data through the extension of participation and triangulation.Results of this study show that the marketing strategy of Culture and Tourism Rokan Hulu is decisive segmentation, perform targeting, promotion through print media and online media. Supporting factors in conducting marketing strategy is the attraction Airpanas Hapanasan an asset in the regions, the object of Hapanasan Airpanas tourists are also breeding butterflies, children's playground as well as outbound, and the location of Rokan Hulu directly adjacent to West Sumatra. Inhibiting factor is the lack of cooperation with a third party / private sector in managing attractions Airpanas Hapanasan the minimnnya intensity of promotion by local governments in promoting attractions Airpanas Hapanasan the professionalism, knowledge in promoting regional tourism is still minimal and competition attractions same become an obstacle to the government in promoting the tourist attraction.Jom